Evolution of Residual Stress, Crystal Orientation, and Texture on Preheating Weld Treatment of Low Carbon Steel ASTM A572 Grade 42 - Saputro, Suratno Adi; Andoko, Andoko; Puspitasari, Poppy (Universitas Negeri Malang, 2024)
Preheating is one type of heat treatment on the material prior to starting the welding process by increasing the temperature of the material. It is used to reduce the cooling rate during the welding processes to minimize the risk of residual stress and cracking during welding. Besides the benefits of welding, it also has a negative impact, especially on the integrity of the material, because the heating process at high temperatures will cause residual stress, which will affect the mechanical properties, chemical composition, and microstructure of the material, especially on Heat Affected Zone (HAZ). This study aims to analyze the effect of preheating at a temperature of 200 ºC on the welding for ASTM A572 Grade 42 steel with a thickness of 40mm using the SMAW (Shielded Metal-Arch welding) method. ASTM A572 Grade 42 was used in this study with carbon content of less than 0.25%. Based on the results of measurements and analysis using the XRD method, it was found that preheating resulted in reducing the residual stress on both weld metal and HAZ areas. Preheating treatment also moved the peak diffraction to the right side, which means the heat treatment affected compressive residual stress rather than tensile residual stress. For crystal orientation, area [110] has the highest peak diffraction and highest intensity. This area also was found with smaller size crystal size and higher dislocation and microstrain. While bigger crystal size with lower dislocation and microstrain were found in the area [200]. For texture, the highest density was found in the area [200], while the weaker texture was found in the areas [110] and [211]. The texture was influenced by plastic deformation due to atomic structure and its dislocation.